New Socioliterary Visions of Saudade: Demystification and Criticism in the Work of Seoane, Valente and Rivas - Fernández Martínez, Antía (Madrygal. Revista de Estudios Gallegos, 2020)
This article presents a brief chronological journey through Galician literature from the mid-twentieth century to the present, personified in the figures of Luís Seoane, José Ángel Valente and Manuel Rivas, in order to analyze how the traditional discourse of saudade is dynamited in their work, creating new conceptions for the term that encompass bigger territories and identities and that restrict much less not only the idea of Galicia, but also our idea of ourselves.
Keywords: Saudade; Morriña (Homesickness); Emigration; Criticism; Demystification; Deterritorialization